Achievement motive, autonomous motivation, and attendance at fitness center: A longitudinal prospective study. (November 2020) - Kopp, Philipp M.; Senner, Veit; Kehr, Hugo M.; Gröpel, Peter
Abstract: Objectives: The aim of this study was to test whether achievement motive, autonomous forms of exercise motivation (intrinsic motivation, identified regulation), and controlled forms of exercise motivation (introjected regulation, external regulation) would predict gym attendance over 30 consecutive weeks in a sample of new gym members. Design: A longitudinal prospective study with four distinct measurement occasions was employed. Psychological variables and gym attendance were assessed in the first, fourth, 15th, and 30th week after starting the membership. Method: Participants were 229 new gym members. The implicit achievement motive was measured using the Picture Story Exercise. The explicit achievement motive and exercise motivations were measured with questionnaires. Gym attendance was obtained via self-reports and also recorded electronically. Multilevel growth modeling was used as the main analysis method. Results: Participants overestimated their self-reported gym attendance; the overall gap between self-reported and actual attendance was 39%. The achievement motive did not predict participants' gym attendance over the 30-week period, neither for self-reported nor for actual. The effect of autonomous motivation was mixed. Intrinsic motivation predicted self-reported, but not actual, gym attendance over the 30-week period, whereas the evolution of intrinsic motivation was unrelated to gym attendance. Identified regulation was unrelated to gym attendance, but the increase in identified motivation over time positively predicted both self-reported and actual gym attendance. Controlled motivation was unrelated to gym attendance. Conclusions: Continuous and regular participation in an exercise program is more likely when individuals enjoy the program and consider it personally important. Highlights: Achievement motive does not predict gym attendance over 30-week period. Maintained autonomous motivation predicts continuous gym attendance. People overestimate their self-reported gym attendance when compared to actual gym attendance.